2021
DOI: 10.1371/journal.pone.0261237
|View full text |Cite
|
Sign up to set email alerts
|

Influence of agriculture on child nutrition through child feeding practices in India: A district-level analysis

Abstract: Malnutrition continues to be a primary concern for researchers and policymakers in India. There is limited scientific research on the effect of agriculture on child nutrition in the country using a large representative sample. To the best of our knowledge, no study has examined the spatial clustering of child malnutrition and its linkage with agricultural production at the district-level in the country. The present study aims to examine agricultural production’s role in improving the nutritional status of Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…From the Asian perspective, India has been identified as a famous nation with the highest rate of wasted children below five years; hence, the country may fail to meet the global 2025 nutrition target for wasting [ 41 ]. Agricultural production poses an influence on child nutrition as it influences child feeding practices [ 42 ]. Many times, agricultural vulnerability to global warming and climate change has been adversely influencing malnutrition among Indian children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…From the Asian perspective, India has been identified as a famous nation with the highest rate of wasted children below five years; hence, the country may fail to meet the global 2025 nutrition target for wasting [ 41 ]. Agricultural production poses an influence on child nutrition as it influences child feeding practices [ 42 ]. Many times, agricultural vulnerability to global warming and climate change has been adversely influencing malnutrition among Indian children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Dietary diversity is a proxy indicator of sufficiency in nutrient density of food consumption in children because less meal frequency indicates inability to meet children’s energy requirements [ 45 ]. Production rate of indigenous food crops, cereals, and pulses determines the minimum acceptable diet, minimum meal frequency, and minimum dietary diversity [ 42 ]. This means that indigenous food production often exhibits significant associations with food security status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A past study reveals the positive impacts of home gardens towards addressing food insecurity and malnutrition, besides benefits such as income and livelihood opportunities for resource-poor families [ 32 ]. Nutrient-sensitive agriculture has also been the best approach to improving children’s nutritional status [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that breastfeeding, maternal education, and income are also important predictors [ 23 25 ]. Environmental factors such as particulate matter 2.5 (PM 2.5 ) and agriculture were found to be associated with childhood undernutrition [ 26 , 27 ]. It can be observed that most previous studies have focused on the demographic and socio-economic determinants of the nutritional status of a child by neglecting the most significant factor—Low Birth Weight (LBW), which is an independent factor contributing to malnutrition among children, primarily in Asian and African countries [ 28 ].…”
Section: Introductionmentioning
confidence: 99%